A Virtual Reality Platform for Analyzing Remote Archaeological Sites - Cassidy, Brendan; Sim, Gavin; Wayne Robinson, David; Gandy, Devlin (Interacting with computers, 2019)
This paper describes a Virtual Reality (VR) prototype developed to help archaeologists and other stakeholders explore and analyse archaeological data in a more immersive context. We describe a VR reconstruction of Pleito Cave, a fragile world class rock-art site with accessibility limitation. Key stakeholders are identified and a prototype is described that provides a VR platform for visualizing and interacting with complex archaeological data (gathered from techniques such as decorrelation stretch and X-ray fluorescence) virtually 'in situ' , in a way that would not be possible at the real site. The prototype allows multiple remote users to interact with the cave together remotely providing opportunities for collaborative interpretation and analysis of archaeological data. We also present a survey-based evaluation in which both archaeologists and Native American stakeholders indicate positive responses for measures of both engagement and value.This paper describes a Virtual Reality (VR) prototype developed to help archaeologists and other stakeholders explore and analyse archaeological data in a more immersive context. We describe a VR reconstruction of Pleito Cave, a fragile world class rock-art site with accessibility limitation. Key stakeholders are identified and a prototype is described that provides a VR platform for visualizing and interacting with complex archaeological data (gathered from techniques such as decorrelation stretch and X-ray fluorescence) virtually 'in situ' , in a way that would not be possible at the real site. The prototype allows multiple remote users to interact with the cave together remotely providing opportunities for collaborative interpretation and analysis of archaeological data. We also present a survey-based evaluation in which both archaeologists and Native American stakeholders indicate positive responses for measures of both engagement and value.